Integrated transcriptome and metabolome analyses reveal the adaptation of Antarctic moss Pohlia nutans to drought stress - Fang, Shuo; Li, Tingting; Zhang, Pengying; Liu, Chenlin; Cong, Bailin; Liu, Shenghao (Frontiers in Plant Science, 2022)
Most regions of the Antarctic continent are experiencing increased dryness due to global climate change. Mosses and lichens are the dominant vegetation of the ice-free areas of Antarctica. However, the molecular mechanisms of these Antarctic plants adapting to drought stress are less documented. Here, transcriptome and metabolome analyses were employed to reveal the responses of an Antarctic moss (Pohlia nutans subsp. LIU) to drought stress. We found that drought stress made the gametophytes turn yellow and curled, and enhanced the contents of malondialdehyde and proline, and the activities of antioxidant enzymes. Totally, 2451 differentially expressed genes (DEGs) were uncovered under drought treatment. The representative DEGs are mainly involved in ROS-scavenging and detoxification, flavonoid metabolism pathway, plant hormone signaling pathway, lipids metabolism pathway, transcription factors and signal-related genes. Meanwhile, a total of 354 differentially changed metabolites (DCMs) were detected in the metabolome analysis. Flavonoids and lipids were the most abundant metabolites and they accounted for 41.53% of the significantly changed metabolites. In addition, integrated transcriptome and metabolome analyses revealed co-expression patterns of flavonoid and long-chain fatty acid biosynthesis genes and their metabolites. Finally, qPCR analysis demonstrated that the expression levels of stress-related genes were significantly increased. These genes included those involved in ABA signaling pathway (NCED3, PP2C, PYL, and SnAK2), jasmonate signaling pathway (AOC, AOS, JAZ, and OPR), flavonoid pathway (CHS, F3',5'H, F3H, FLS, FNS, and UFGT), antioxidant and detoxifying functions (POD, GSH-Px, Prx and DTX), and transcription factors (ERF and DREB). In summary, we speculated that P. nutans were highly dependent on ABA and jasmonate signaling pathways, ROS scavenging, flavonoids and fatty acid metabolism in response to drought stress. These findings present an important knowledge for assessing the impact of coastal climate change on Antarctic basal plants.